Penerapan Pembelajaran Berbasis Masalah untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas XII-MIA-3 MAN 1 Kota Bima Pada Semester Genap Tahun Pelajaran 2021/2022 - Siti Hadiah (Literasi: Jurnal Pendidikan Guru Indonesia, 2023)
The purpose of this research is to describe the learning outcomes and increase in student learning activities. This research is a class action research (CAR) designed in two cycles. This research was conducted in Class XII-MIA-3 MAN 1 Kota Bima in the Even semester of the 2021/2022 Academic Year. The results of this study indicate that; 1) The application of problem-based learning can improve student learning outcomes in learning mathematics in Class XII-MIA-3 MAN 1 Kota Bima. Improved learning outcomes can be seen from the test results of meetings 1 and 2 cycle I and also the results of tests at meetings 1 and 2 cycle II. This increase in learning outcomes is due to students experiencing a learning process where students can find answers to problems formulated by the teacher based on the data and facts they have obtained and can generalize the knowledge they have obtained; 2) the use of problem-based learning can increase student learning activities in learning mathematics in Class XII-MIA-3 MAN 1 Kota Bima. The increase occurred from each meeting of each cycle and from cycle I to cycle II. Students are also interested in paying attention to the material being presented and have the courage to ask questions related to the material being studied. This can be seen from the average score of students in cycle 1, which is equal to 78.00 and the average value of students in cycle II is .84.83 so that there is an increase of 6.83. Meanwhile, if seen from the percentage of students who did not complete the Cycle I was 33% and 67% completed. Meanwhile in cycle II, only 6% remained incomplete and 93% completed.